Immunoglobulin-G Glycation by Fructose Leads to Structural Perturbations and Drop Off in Free Lysine and Arginine Residues - Faisal, Mohammad; A. Alatar, Abdulrahman; Ahmad, Saheem (Protein and Peptide Letters, 2017)
Non-enzymatic glycation is the addition of free carbonyl group of reducing sugar to the free amino groups of proteins and leads to the formation of early glycation products and further into advanced glycation end products (AGEs). Fructose reacts rapidly with the free amino groups of proteins to form AGEs. AGEs are believed to be involved in the pathogenesis of several diseases, particularly in diabetic complications. In this study, IgG was glycated with fructose monosaccharide at 10 mM concentration for varying time interval. The reaction mixture was kept at 37ºC. The early glycation of IgG was done by nitroblue tetrazolium assay (NBT), and the generation of AGEs was done by the extent of side chain modifications (lysine and arginine), N-carboxymethyl lysine, pentosidine and carbonyl content. The decrease in free lysine and arginine residues suggests that protein ‘IgG’ has undergone modification specifically on epsilon amino groups of lysine and arginine. Additionally, their fluorescence and absorbance characteristics were also systematically studied. The results suggest that the maximum Amadori product (ketoamine content) was formed on sixth day of the incubation. The conformational structural perturbation was observed within the glycated IgG protein as studied by using various physicochemical techniques. This study reports structural perturbation, formation of various intermediates and AGEs.
Keywords: AGEs